2013
DOI: 10.1186/1471-2407-13-508
|View full text |Cite
|
Sign up to set email alerts
|

Using Twitter for breast cancer prevention: an analysis of breast cancer awareness month

Abstract: BackgroundOne in eight women will develop breast cancer in her lifetime. The best-known awareness event is breast cancer awareness month (BCAM). BCAM month outreach efforts have been associated with increased media coverage, screening mammography and online information searching. Traditional mass media coverage has been enhanced by social media. However, there is a dearth of literature about how social media is used during awareness-related events. The purpose of this research was to understand how Twitter is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
154
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(170 citation statements)
references
References 24 publications
8
154
2
6
Order By: Relevance
“…To investigate the impact of health (related) organizations on Twitter, we define health organizations as those Twitter accounts with more than 5, 000 followers and at least one of the following keywords in their Twitter profile (an ap-proach borrowed from (Thackeray et al, 2013)): {cancer, health, pharmacy, pharmaceutical, campaign, government, firm, company, companies, news, group, society, committee, volunteer, we, official, marketing, promotions and forum).}. The overlap between both types of users (well-known vs. organizations) is between 2.2% (US) and 30.7% (Australia).…”
Section: From Hypotheses To Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the impact of health (related) organizations on Twitter, we define health organizations as those Twitter accounts with more than 5, 000 followers and at least one of the following keywords in their Twitter profile (an ap-proach borrowed from (Thackeray et al, 2013)): {cancer, health, pharmacy, pharmaceutical, campaign, government, firm, company, companies, news, group, society, committee, volunteer, we, official, marketing, promotions and forum).}. The overlap between both types of users (well-known vs. organizations) is between 2.2% (US) and 30.7% (Australia).…”
Section: From Hypotheses To Measurementsmentioning
confidence: 99%
“…While Thackeray et al (2013) and Bravo and Hoffman-Goetz (2015) investigated the change of people's awareness during social media health campaigns, to our knowledge no research so far has considered the second goal of many health campaigns -raising funds for research and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…22 Another study found that tweeting about breast cancer did not promote any specific preventive behavior and is mostly used as a one-way communication tool. 9 However, anonymous online forums, such as message boards and support groups, provide information, emotional support and an avenue for selfexpression. 23 Future research could focus on determining why individuals choose to share health information on social media and what they hope to obtain from it, as well as why others choose not to do so.…”
Section: Content Analyses Of Breast Cancer Specific Facebook Groupsmentioning
confidence: 99%
“…5,8,9 One such public health issue is breast cancer. It is the second leading cause of cancer mortality in women, with an estimated 230,815 new cases and 40,860 associated deaths in 2013.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation